Blood pressure and hypertension in older adults with a history of regular cannabis use: findings from the Multi-Ethnic Study of Atherosclerosis - Corroon, Jamie; Bradley, Ryan; Allison, Matthew A.; Grant, Igor (Frontiers in Cardiovascular Medicine, 2024)
Background Observational evidence investigating associations between cannabis use and blood pressure and hypertension is inconsistent. Methods Cross-sectional data from 3,255 participants at Exam 6 (2016–2018) of the Multi-Ethnic Study of Atherosclerosis (MESA) were analyzed, including self-reported cannabis smoking patterns, standardized measures of systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP; BP collectively), and hypertension. ANCOVA and multivariable relative risk regression models were used to calculate adjusted means for BP and adjusted prevalence ratios (PRs) for prevalent hypertension. Results In fully adjusted ANCOVA models, a history of regular cannabis smoking, when compared to no history, was not significantly associated with increased SBP [mean difference: 0.1 mmHg (95% CI: −1.6–1.9)], DBP [mean difference: 0.5 mmHg (95% CI: −0.3–1.4)], PP [mean difference: −0.5 mmHg (95% CI: −1.8–0.9)], or prevalent hypertension [PR: 1.01 (95% CI: 0.93−1.10)]. Furthermore, no associations were observed for either the duration or recency (in the past month) of cannabis smoking or number of joint/pipe years. Models exploring potential interactions between a history of regular cannabis smoking and age, sex, race/ethnicity, and cigarette smoking status were not significant for either BP or hypertension. Conclusions In a cohort of racially and ethnically diverse older adults with a high prevalence of hypertension, no evidence of increased risk due to regular cannabis smoking was found for either blood pressure or hypertension.